Infective endocarditis in a Finnish tertiary care hospital : from etiology to embolic events - Ahtela, Elina; Kytö, Ville; Vahlberg, Tero; Hohenthal, Ulla; Ekström, Tommi; Porela, Pekka; Oksi, Jarmo (Taylor & Francis, 2025)
Background
In this study in a tertiary care hospital, we examined the characteristics of the different microbial etiologies of infective endocarditis (IE) and the factors associated with embolic events.
Materials and methods
We included patients (aged ≥18 years) hospitalized for IE in Turku University Hospital in Finland between 2004-2017. Patient data were derived retrospectively from the mandatory database and patient record system.
Results
Among 342 IE cases in 321 patients, Staphylococcus aureus was isolated in 33.9%, viridans group streptococci in 18.3% and enterococci in 8.8% of the cases. Patients with enterococcal IE had more often a prosthetic valve (p < 0.001), recent major healthcare procedure or hospital admission (p < 0.001) and heart failure during admission (p = 0.006) than the patients with other etiologies. Viridans group streptococci and enterococci vs. S. aureus were associated with a lower rate (OR 0.34, p = 0.007 and OR 0.20, p = 0.006, respectively) and IE of the multiple valves vs. aortic valve with a higher rate (OR 2.30, p = 0.043) of all embolic events but not cerebral embolisms when analyzed separately. Both all embolic events and cerebral embolisms were strongly associated with the occurrence of an echocardiography-disclosed vegetation (OR 3.31, p = 0.004 and OR 2.73, p = 0.019, respectively).
Conclusions
Our study suggests that enterococcal IE is often associated with a previous healthcare procedure or hospital admission and heart failure. Staphylococcus aureus etiology and IE of the multiple valves are associated with a higher rate of all embolic events but not cerebral embolisms. Echocardiography-disclosed vegetation is associated with a higher occurrence of embolisms.